Dynamic Simulation of Gear Tooth under Two Crack Affecting Lines - Cui Lingli; Zhai Hao; Zhang Feibin (Jixie chuandong)
For the purpose of investigating the effect of crack affecting lines on the gear tooth vibration response,the energy method is used for meshing stiffness calculation,and the effect of two crack affecting lines on meshing stiffness are compared with each other.The accuracy of solving meshing stiffness under crack curve affecting line is proved by the finite element method.Then a dynamics model of gear tooth is built to compare the different responses of gear system under the two crack affecting lines.The result shows that an intersection will appear in the fault detection indicators under two crack affecting lines when the crack size grows up to the special value and the intersection which is different from previous paper is proved to be right.